Analisis Manajemen Mutu Menggunakan Standar ISO 9001:2015 Klausul 7 Pada PT XYZ - Darmadi, Darmadi; Setiawan, Johan (Journal of Business, Management, and Social Studies, 2021)
The objective of this study is to give company suggestions from ISO 9001:2015 clause 7 to improve their readiness before implementing ISO 9001:2015. This research uses quantitative method research distributed to 3 people out of 4 people in the business analyst division and three people out of 5 people in the developer division for the questionnaire, and for the interview, the interviewees are representatives of the company who can ensure that the information provided is accurate and in accordance with reality. This research found two suggestions for the company to improve its readiness before implementing ISO 9001:2015. The first suggestion for sub-chapter 7.2 regarding competence is to hold training on third-party applications that can be integrated with the company's IT products, and the second suggestion is for sub-chapter 7.3 regarding awareness, to increase employee awareness of the importance of quality management, training on ISO 9001:2015 needs to be held. By analyzing company readiness, the company can know its readiness before implementing ISO 9001:2015, and the company can improve based on this research.